Length-weight relationship in the catfish Horabagrus brachysoma (Gunther) - Kumar, G Sunil; Anna Mercy, T V; John, K C (Indian Journal of Fisheries, 2011)
Horabagrus brachysoma (Gunther) is an endangered catfish endemic toKerala. In the present study an attempt is made to study the length-weightrelationship of this species. It is found that both males and females have anisometric growth pattern. Hence the determined regression equation can beused for calculating the weight of a fish from given length